Program Keluarga Harapan: Can It Reduce Poverty and Increase Welfare in Indonesia? Household Level Evidence from Districts/Cities in Indonesia on 2019 - Resina, Dela; Kamarni, Neng; Putra, Febriandi Prima (Jurnal Samudra Ekonomi dan Bisnis, 2023)
Poverty is a multidimensional phenomenon which is a major challenge in all countries. To reduce poverty and improve welfare, government intervention programs are needed. Conditional cash transfer programs are widely implemented in several countries. In Indonesia, there is Program Keluarga Harapan (PKH). This program has many debates as an anti-poverty program. This research looks at the effect of PKH on poverty and welfare in Indonesia. It used the 2019 Susenas raw data and analyzed by SEM-PLS method. The findings showed that PKH had a negative-significant effect on poverty and a positive-significant effect on welfare in Indonesia. In addition, poverty has a negative and significant effect on welfare in Indonesia. The research results are expected to be input for the central and regional governments in making policies for the sustainability of PKH implementation in reducing poverty and increasing welfare.